Growth rates of Eucheuma cottonii and Eucheuma spinosum in the occasionally exposed and fully submerged environments - Baltazar, Gonchio Que
A study to test the effect of occasionally and fully submerged environments and three water depths (5,10 and 15 cm) on the growth of E. cottonii and E. spinosum was conducted at Tawi-Tawi, Philippines from December, 1983 to March, 1984 in a randomized Complete Block Design. The seedlings of both species with an initial weight of 110 g. per seedling were tied to monofilament nylon string and planted at desired distances by trying the ends of the nylon string to the wooden stakes fixed earlier. The results indicate that both environments had comparable soil and water properties except the water depth which was deeper in the fully submerged environment. The organic matter content in fully submerged environment was also higher than the other. The soils of both environment had high levels of potassium. The growth of E. cottonii in terms of length of sub thalli, sub-sub thalli, their number and weight per plant was higher than E. spinosum. The growth of both species in terms of same components listed above was also higher in fully submerged environment than occasionally exposed environment. The effect of planting distance on the growth of the two species in both environments was insignificant. The profuse growth of other seaweeds and aquatic plants negatively affected the growth of both species in the latter environment. There was no growth of weeds in fully submerged environment. In general, the growth of E. spinosum because of its fragile nature and susceptibility to adverse conditions such as strong waves was poorer than E. cottonii. The growth of both species ceased after two months of culture period.